Antioxidant Activity and Phytochemical of Ocimum basilicum to Strengthen the Traditional Balinese Medicine System - I Nyoman Arsana; Ni Ketut Ayu Juliasih; A. A. Ayu Sauca Sunia Widyantari (Biosaintifika: Journal of Biology & Biology Education, 2023)
The system of traditional Balinese medicine is known as Usada. One type of plant used in Usada is basil (Ocimum basilicum L). Antioxidant activity and phytochemical of ethanol extracts of two varieties of basil, Ocimum basilicum L (var.) Bali (OcB) and Ocimum basilicum L (var.) Lombok (OcL) was investigated.  Total phenol was determined by folin-cioccalteu phenol reagent, total flavonoid by quarsetine reagent, tannin by Folin-Denis reagent, and antioxidant activity was determined using the 2,2-diphenyl-1-picrylhydrazyl radical scavenging method and is expressed as IC50. All of the parameters were measured by spectrophotometer. Phytochemicals were determined by Gas chromatography and mass spectrometry (GC-MS) Analysis. Morphological characters (stems, leaves, and flowers) are also observed. The results showed, in OcB obtained 92 compounds, 10 of which are important compounds that have an antioxidant effect, while in OcL 139 compound components were found, 15 of which are important compounds. Levels of phenols, flavonoids, tannins, as well as IC50 in OcB are; 3526.65 mg GAE/100g, 15841.6795 mg QE/100g, 2402.80 mg/100 g, and 24.9410 mg/L, respectively, while in OcL respectively are; 3297.71 mg GAE/100g, 13242.30 mg QE/100g, 850.71 mg/100, and 33.1105 mg/L. Conclusions, morphologically OcB and OcL showed no difference except leaf width and petiole length. The antioxidant activity of OcB is better, as well as higher levels of phenols, flavonoids, and tannins compared to OcL.